Szervezetfejlesztés lehetőségei egy konkrét államigazgatási szervnél, egy felmérés eredményei alapján - Elekes, Edit (Közép-Európai Közlemények, 2014)
Law enforcement departments as open organizations carry out their work in a constantly changing system of micro- and macro-environments. Their work is, at the same time, strictly regulated by laws and regulations. Organization development comprises the reactions and responses given, with the support and encouragement of the leadership, by the organization concerned to the changes of the environment, and also the methods used by the leadership in order to improve the operation of the organization concerned. A police department is an authority, and at the same time it is a service provider to the general public. This duality of roles requires two different types of connection network and management style. Leadership is closely interrelated with organization development, and as an officer in the police force I was actively involved in that kind of work. My task was putting forward the results of a specific organization development and change management project, based upon a primary survey that I conducted myself. A part of the survey is still in progress. My survey is partly based upon an earlier model project that included a questionnaire research carried out in the Carpathians Euroregion and partly upon the self-assessment of the police force concerned. The research is a part of my doctoral procedure, and is expected to contribute to the verification of the managament theory hypotheses that I set up previously.